Liver metabolomic profiles of sea lamprey (Petromyzon marinus) are influenced by sex and maturation stages - Tamrakar, Sonam; Huerta, Belinda; Chung‐Davidson, Yu‐Wen; Li, Weiming (Metabolomics, 2025)
INTRODUCTION: Sea lamprey (Petromyzon marinus) is a unique vertebrate model to examine how liver metabolomes support different reproductive functions. Juvenile sea lamprey prey on other fish species by attaching to their body and feeding on their blood and body fluids. Once reaching adulthood, they cease feeding, migrate to spawning streams and begin their final sexual maturation. During these processes, the male livers produce large quantities of bile acid pheromone precursors to be modified and released via gills, whereas the female livers synthesize vast amounts of vitellogenin (yolk lipophosphoprotein) to be transported to the ovary. OBJECTIVE: We aim to test the hypothesis that the liver metabolic pathways exhibit dramatic changes during sexual maturation of sea lampreys that support their reproductive strategies. METHODS: Liver tissues from prespermiating (PSM) and spermiating (SM) males, and preovulatory (POF) and ovulatory (OF) females were homogenized, extracted and analyzed using the Thermo Q-exactive Orbitrap UPLC/MS/MS. Progenesis QI, Compound Discoverer, and Metaboanalyst were used for alignment, peak picking, deconvolution, and annotation. Data were subjected to analyses such as PCA and PLS-DA, using the SIMCA® software. The glycogen and triglyceride content in liver were also examined to determine levels of stored energy. RESULTS: Overall, we found upregulations of amino acid and fatty acid metabolisms in mature male sea lamprey compared to the immature ones. Although the metabolic differences were comparatively subdued in the sexually immature males and females, amino acid regulation was slightly higher in females. CONCLUSION: We conclude that the metabolic dynamics in sea lamprey livers are consistent with their reproductive strategies.
Keywords: Bile acids; Bioinformatics; Biology; Computational biology; Fatty acids; Fishery; Hepatic Physiology; Hepatocytes; Hepatology; Lamprey; Maturation; Metabolism; Metabolomics; Petromyzon; Petromyzon marinus; Reproductive Physiology; Sex; Untargeted metabolomics; Zoology; dept.che; peer-reviewed

Plasma metabolomic profiles reveal sex- and maturation-dependent metabolic strategies in sea lamprey (Petromyzon marinus) - Tamrakar, Sonam; Huerta, Belinda; Chung-Davidson, Yu-Wen; Li, Weiming (Metabolomics: Official Journal of the Metabolomic Society, 2022)
INTRODUCTION: Adult sea lamprey (Petromyzon marinus) cease feeding and migrate to spawning streams where males build nests, undergo final sexual maturation, and subsequently produce and release large quantities of bile acid pheromones that attract mature females. These animals are predicted to rearrange their metabolic pathways drastically to support their reproductive strategies, presenting advantageous opportunities to examine how sex and the maturation processes affect metabolism. OBJECTIVES: The objective is to investigate the metabolic differences between sexes and maturation states in sea lamprey that support changes in physiological functions. METHODS: We compared plasma metabolomes of spawning and prespawning sea lamprey in both sexes using both non-targeted and targeted metabolomics approaches using UPLC/MS-MS with electrospray ionization in both positive and negative modes. The data were processed using Progenesis QI, Compound Discoverer and XCMS softwares for alignment, peak picking, and deconvolution of the peaks. Principle component analyses (PCA) and partial least squares discriminant analyses (PLS-DA) were performed using SIMCA and Metaboanalyst softwares to identify discriminating features, followed by fragmentation matching with extensive database search and pathway mapping. RESULTS: The pheromonal bile acid biosynthesis was upregulated significantly in males compared to females. Spermiating males further upregulated bile acid biosynthesis by altering amino acid metabolisms, upregulating cofactors and nucleotide metabolisms, but downregulating carbohydrate and energy metabolisms. CONCLUSION: Plasma metabolomes are sex- and maturation-dependent and reflect the special metabolic demands at each life stage and reproductive strategy.
Keywords: Animals; Bile Acids and Salts; Bile acid biosynthesis; Female; Male; Metabolic pathways; Metabolomics; Petromyzon; Petromyzon marinus; Sexual Maturation; Sexual selection; Tandem Mass Spectrometry; Targeted analyses; Untargeted analyses; dept.che; peer-reviewed

Spatiotemporal Patterns in Profiles of Amino Acids Indicates They Are Unlikely Singular Olfactory Cues Underlying Natal Homing in Migratory Fishes - Kimmel, Jacob; Buchinger, Tyler; Tamrakar, Sonam; Huerta, Belinda; Larson, Douglas; Baker, Edward; Zorn, Troy; Scribner, Kim; Li, Weiming (Freshwater Biology, 2025)
ABSTRACT Migratory fishes are renowned for their ability to home to natal streams for spawning. Learned olfactory cues play a critical role in natal homing of Pacific salmon and other fishes, but the underlying chemical signature of streams remains poorly understood after decades of study. The molecules that convey a stream‐specific odour must differ among sites but remain constant over time. Among leading odorant candidates are amino acids; however, little research has assessed the spatial and temporal variability of amino acid profiles in streams. We report a comprehensive chemical study of dissolved amino acids as potential olfactory cues for homing by migratory fish. Specifically, we profiled amino acids in water from 23 streams in the upper Laurentian Great Lakes basin over 2 years. We investigated variation in amino acid profiles (1) among regions and rivers within a year, (2) between years and (3) among sites and across the seasons of migration and early life history within a stream. Liquid‐chromatography tandem mass spectrometry revealed nanomolar concentrations for most of the 20 L‐amino acids measured, above the levels detectable by studied migratory fishes. Moreover, amino acid profiles were temporally stable between 2 years and across an annual season from adult spawning migration through offspring early‐life development within a stream. However, spatial differences in amino acid profiles were evident primarily over large geographic distances (among regions) but not among tributaries within regions or among sites within a stream. Collectively, our results indicate dissolved amino acids may be consistent components of rivers' odorant profiles but suggest additional molecules are likely important for natal homing of migratory fishes to specific spawning sites. We suggest that future studies consider the combined importance of amino acids and molecules from other chemical classes. Understanding the chemical basis of olfactory‐guided natal homing is especially important as human activities could alter the odorant profiles of streams and thereby disrupt fish migrations and negatively impact population recruitment.
Keywords: Biology; Ecology; Evolutionary biology; Great Lakes; Homing (biology); Neuroscience; Olfaction; Olfactory cues; Olfactory system; Zoology; dept.che; navigation; olfactory imprinting; peer-reviewed; site fidelity; sturgeon